IMPACT OF THE MILITARY CONTROL ON THE PROCESS ISLAMIC EDUCATION IN SCHOOL CONFLICT SASNUPATAM, PATTANI SELATAN, THAILAND - zikry septoyadi; Vita Candrawati (Penerbit Hellow Pustaka, 2025)
This research uses a qualitative approach. The subjects of this study were the principal, Ustadz, and Sasnupatam school students, South Pattani, Thailand. The object of research in the form of the impact of military control that controls the school. The technique used in determining the subject of this study uses the Purposive Sampling technique, which has specific criteria that can strengthen a person's reason for being a research subject—data collection techniques with the method of observation, interviews, and documentation. The results of this study indicate that; 1) with military control in Sasnupatam schools, some teachers do not feel there are problems with military control, but for students who feel uncomfortable in the presence of military control, because they can have the effect of overall military control; 2) the positive impact materially has the advantage of getting the school's confidence from the kingdom that the school does not violate laws or school laws and get an education budget. Can be psychologically positive, that is a sense of comfort arises with military control because it can balance between teachers and the military; 3) the material negative impact of a teacher / instructor must explain to the military and spend a considerable amount of time and have an impact on the teaching-learning process in the classroom. Psychologically negative impact that is affecting the psychic teacher and students. Students cannot accept Pattani's historical material and jihad, besides there is a sense of discomfort teachers and students on the grounds of military control is not appropriate if the target school.